2020
DOI: 10.1101/2020.10.18.344622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An engineered decoy receptor for SARS-CoV-2 broadly binds protein S sequence variants

Abstract: The spike S of SARS-CoV-2 recognizes ACE2 on the host cell membrane to initiate entry. Soluble decoy receptors, in which the ACE2 ectodomain is engineered to block S with high affinity, potently neutralize infection and, due to close similarity with the natural receptor, hold out the promise of being broadly active against virus variants without opportunity for escape. Here, we directly test this hypothesis. We find an engineered decoy receptor, sACE22.v2.4, tightly binds S of SARS-associated viruses from huma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 52 publications
(45 reference statements)
3
80
0
Order By: Relevance
“…Among the mutations described in the B.1.1.7 variant, the N501Y mutation, localised in the receptor binding site has been shown to increase the binding of SARS-CoV-2 to the angiotensin-converting enzyme 2 (ACE2) host receptor [29], inferring increased viral fitness and transmission properties. Although some data suggest that this variant may escape the neutralisation by select convalescent sera and therapeutic monoclonal antibodies, sera from participants of a trial of the mRNA based COVID vaccine BNT162b2 neutralised with similar efficacy the wild type N501 and the variant N501Y [30] suggesting retained vaccine efficacy against the B.1.1.7 variant.…”
Section: Discussionmentioning
confidence: 99%
“…Among the mutations described in the B.1.1.7 variant, the N501Y mutation, localised in the receptor binding site has been shown to increase the binding of SARS-CoV-2 to the angiotensin-converting enzyme 2 (ACE2) host receptor [29], inferring increased viral fitness and transmission properties. Although some data suggest that this variant may escape the neutralisation by select convalescent sera and therapeutic monoclonal antibodies, sera from participants of a trial of the mRNA based COVID vaccine BNT162b2 neutralised with similar efficacy the wild type N501 and the variant N501Y [30] suggesting retained vaccine efficacy against the B.1.1.7 variant.…”
Section: Discussionmentioning
confidence: 99%
“…All three variants or lineages of concern harbor a suite of mutations in the spike protein, which is required for host cell entry by binding to the angiotensin-converting enzyme-2 (ACE-2) receptor. In particular, B.1.1.7, B.1.351, and P.1 share an N501Y mutation that increases ACE2 receptor binding affinity (Chan et al 2020;Starr et al 2020) and cell infectivity in animal models (Gu et al 2020) and likely contributes to the increased transmission observed for B.1.1.7 and B.1.351 (Tegally et al 2020;Davies et al 2021;Volz et al 2021). The mutations K417N and E484K found in B.1351 and P.1 dramatically reduce the neutralization activity of monoclonal antibodies and convalescent plasma/sera (Weisblum et al 2020;Cele et al 2021;Liu et al 2021;Wibmer et al 2021;Greaney et al 2021), making them of considerable concern for vaccine efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation is of particular concern because it is located in the viral receptor binding site for cell entry, increases binding to the receptor (angiotensin converting enzyme 2), and enables the virus to expand its host range to infect mice. 5,6 We generated an isogenic Y501 SARS-CoV-2 on the genetic background of the N501 clinical strain USA-WA1/2020, which also provided the genetic background of the BNT162b2-encoded spike antigen. Sera of 20 participants in the previously reported trial, 1,2 drawn 2 or 4 weeks after immunization with two 30-µg doses of BNT162b2 spaced three weeks apart, were tested for neutralization of N501 and Y501 viruses by a 50% plaque reduction neutralization assay (PRNT50; Figure 1).…”
mentioning
confidence: 99%